The Implementation of the Teams Games Tournament Model Assisted by Kahoot in Imlā’ Learning for Students - Rahma, Aufa; Nikmah, Ainun; Huda, Nurul; Syamsiyah, Dailatus; Ardiani, Adina (Mantiqu Tayr: Journal of Arabic Language, 2026)
Imlā’ learning in Arabic language education often encounters challenges related to students’ low writing accuracy and limited classroom engagement. Conventional teaching methods tend to be less interactive, which affects students’ motivation and learning outcomes. This study aims to describe the implementation of the Kahoot-assisted Teams Games Tournament learning model in Arabic Imlā’ learning for first-semester students of the Arabic Language Education Program at State Islamic University Sunan Kalijaga Yogyakarta. This research employed a descriptive qualitative approach conducted during the Field Study Program from October to December 2025. The participants consisted of all first-semester students of Class C selected through total sampling. Data were collected through classroom observations, documentation of learning activities, analysis of students’ written works, and Kahoot quiz results. The findings indicate that the integration of the Teams Games Tournament model with Kahoot created an interactive and collaborative learning environment that increased students’ participation, motivation, and writing accuracy, particularly in applying Arabic orthographic rules (qawāʿid al-imlāʾ) related to hamzah (including hamzah waṣl and hamzah qaṭʿ), alif layyinah (alif mamdūdah and alif maqṣūrah), and the distinction between tāʾ marbūṭah and tāʾ maftūḥah. This study contributes to Arabic language pedagogy by providing practical evidence on the integration of cooperative learning models and digital game-based media in Imlā’ instruction at the university level. Future research is suggested to apply experimental designs, involve broader participant groups, and examine the long-term impact of this learning model on other Arabic language skills.